PENDAMPINGAN PEMBUATAN MATERI SEKOLAH DENGAN PERPLEXITY AI UNTUK GURU SEKOLAH NEGERI KALIDERES - Mawardi, Viny Christanti; Ricky Cangniago; Saskia Lavinsky (Jurnal Serina Abdimas, 2025)
This community service activity aimed to provide training on using Perplexity AI for creating learning materials for elementary school teachers in the Kalideres area, West Jakarta. The training involved 24 elementary school teachers from 11 different schools and used a descriptive qualitative approach to analyze the implementation process and outcomes. The methods included observation, documentation, and evaluation through questionnaires distributed to participants. The workshop consisted of several stages: introduction to artificial intelligence in education, demonstration of Perplexity AI features and benefits, hands-on practice sessions for creating curriculum-appropriate learning materials, discussions and feedback, and activity evaluation. The results showed that 96% of participants gave high ratings (scores 4 and 5 on a scale of 1-5) for the overall workshop activities, with the majority of participants giving a score of 5 (excellent) for almost all evaluation aspects. Participants provided very positive feedback, stating that this training was very interesting, insightful, and beneficial for improving their teaching abilities, especially in creating more innovative learning materials. Despite receiving positive responses, participants also provided constructive suggestions for improvement, including extending training duration, improving technical facilities, and organizing continuous programs with more diverse AI materials. The training successfully demonstrated how AI can assist teachers in efficiently creating systematic and easily understood learning materials while maintaining the essential human role in education. This activity also successfully improved teachers' digital literacy and motivated them to further explore the use of AI technology in their teaching activities. ABSTRAK Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memberikan pelatihan penggunaan Perplexity AI dalam pembuatan materi pembelajaran bagi guru sekolah dasar di wilayah Kalideres, Jakarta Barat. Pelatihan melibatkan 24 guru sekolah dasar dari 11 sekolah berbeda dan menggunakan pendekatan deskriptif kualitatif untuk menganalisis proses pelaksanaan dan hasilnya. Metode yang digunakan meliputi observasi, dokumentasi, dan evaluasi melalui formulir yang disebarkan kepada peserta. Workshop terdiri dari beberapa tahapan: pengenalan kecerdasan buatan dalam pendidikan, pemaparan fitur dan manfaat Perplexity AI, sesi praktik langsung pembuatan materi pembelajaran sesuai kurikulum, diskusi dan umpan balik, serta evaluasi kegiatan. Hasil menunjukkan bahwa 96% peserta memberikan penilaian tinggi (nilai 4 dan 5 dari skala 1-5) terhadap keseluruhan kegiatan workshop, dengan mayoritas peserta memberikan nilai 5 (sangat baik) untuk hampir semua aspek evaluasi. Peserta memberikan umpan balik yang sangat positif, menyatakan bahwa pelatihan ini sangat menarik, menambah wawasan, dan bermanfaat untuk meningkatkan kemampuan mengajar mereka, terutama dalam pembuatan materi pembelajaran yang lebih inovatif.Meskipun mendapat respons positif, peserta juga memberikan saran konstruktif untuk perbaikan, antara lain perpanjangan waktu pelatihan, perbaikan fasilitas teknis, dan penyelenggaraan program berkelanjutan dengan materi AI yang lebih beragam. Pelatihan berhasil menunjukkan bagaimana AI dapat membantu guru dalam membuat materi pembelajaran yang sistematis dan mudah dipahami secara efisien sambil tetap mempertahankan peran penting manusia dalam pendidikan. Kegiatan ini juga berhasil meningkatkan literasi digital guru dan memotivasi mereka untuk mengeksplorasi lebih lanjut penggunaan teknologi AI dalam aktivitas mengajar.